Assessing two rapid quenching techniques for the production of La‐Fe‐Si magnetocaloric alloys in reduced annealing time. Issue 6 (7th August 2019) - Potnis, Gaurav; Krautz, Maria; Waske, Anja; Das, Jayanta; Eckert, Juergen
Abstract: In the present study, we compare a La‐Fe‐Si‐based alloy doped with Mn, LaFe11.7 Si1.2 Mn0.1, cast by three different techniques leading to different microstructures. Arc melting, suction casting, and melt spinning are used to fabricate LaFe11.7 Si1.2 Mn0.1 samples to analyze the influence of as‐cast microstructure and distribution of phases on annealing time required to obtain a magnetocaloric 1:13 phase. The microstructure and phase compositions of both the as‐cast and the annealed samples are analyzed by X‐ray diffraction and electron microscopy. We show that suction casting and melt spinning lead to a significant reduction of the annealing time from 7 days (conventionally cast samples) to 3 days and 1 day, respectively, to obtain the 1:13 phase as a major phase. In these samples, a magnetic entropy change of ∆ S M  = 11 and 8 J/kg·K, respectively, is achieved in the vicinity of T C .